The "Soaring Eagle" : Anatomy of the Polish Take-Off in the 1990's. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Poland stands out among transition economies as having experienced a relatively short and shallow contraction followed by sustained, vigorous growth. This paper examines various aspects of Poland's growth performance from 1992 through 1998 at the macroeconomic level as well as across sectors and regions. It discusses the sources of Poland's growth, showing that early in the decade, improved resource utilization was the paramount determinant, while factor accumulation, supported by rising foreign direct investment inflows, took on increasing importance in the later 1990s.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet